Factors Associated with the Onset of Ovarian Activity of Cattle Commonly Reared in the Huasteca Veracruzana, Mexico (Agro Productividad, 2021)
Objective: To identify the factors that affect the onset of ovarian activity in prepuberal heifers in the Huasteca Veracruzana of Mexico.Design/Methodology/Approach: Samples were taken from animal production units of the municipality of Tantoyuca, Veracruz. The onset of ovarian activity was determined by the presence of ovarian follicles andncorpus luteum by ultrasonography technique. Zoometric indices and body condition were calculated at them same time, and the zootechnical practices that were applied to the animals in the last six months before thesampling day were registered. A survey was applied to characterize the management of animal productionunits; the main topics in the survey were: health, reproduction, nutrition, and suckling. All animals available within selection criteria in the production units were sampled. A multiple linear regression (Statistical Analysis Software Version 9.4) and cluster analysis (R Studio Version 1.1.419) were used to identify the main categorical variables that affected the model.Results: The onset of ovarian activity depends mainly on the anatomical development of the heifers. The biostimulation (male effect) on the heifers has an important effect on reducing the age at puberty.Study Limitations/Implications: The study was developed during a long drought period in the region.Findings/Conclusions: The genetic mosaic of the evaluated animals in the production units did not affect the onset of ovarian activity of the heifers; however crossbred heifers (Bos taurus ? Bos indicus) begin the ovarian activity younger.